Sports detraining, a vital alternative for high-performance youth water polo athletes/El desentrenamiento deportivo, una alternativa vital en atletas juveniles de polo acuático de alto rendimiento - Armando Marin Rojas; Yamila Caridad Camero Reinante; Luis Ángel García Vázquez; Magda Alina Rabassa López- Calleja; José Adolfo Frontela López (Universidad de Pinar del Río "Hermanos Saíz Montes de Oca", 2021)
At present, in Cuba, many athletes who reach their retirement age do not carry out sports detraining processes, which affects their health in the medium term; they begin to suffer from chronic non-communicable diseases, as well as depression and inadequate psychological states. The objective of this research was to determine the inadequacies derived from the conduction of the sports detraining process in retired athletes. To achieve the proposed goals, the authors relied on theoretical and empirical methods; the descriptive statistics tool (percentage calculation) was used to process the information, taking as a sample retired youth water polo athletes, sports doctors, psychologists and sports medicine physiotherapists, to whom interviews were applied and their opinions during the conduction of this process were analyzed. The final result was that there is insufficient knowledge of how to carry out this sports detraining process in the sample studied, they do not fully master the methods, procedures, contents and methodologies, based on the research and methodological preparations on the subject that is vital in high performance sports. Among the most relevant conclusions of this work, it is found that the theoretical references of sports detraining currently do not meet the expectations of the athletes who retire in the various sports groups and the athletes when they retire do not have information on how to carry out this process.